Structure and stability of sodium-caseinate-stabilized oil-in-water emulsions as influenced by heat treatment. (May 2017) - Liang, Yichao; Gillies, Graeme; Matia-Merino, Lara; Ye, Aiqian; Patel, Hasmukh; Golding, Matt
Abstract: The emulsion stability and rheological properties of heated (120 °C, 0 – 60 min) 30% w/w oil-in-water emulsions (droplet diameter ∼ 0.73 μm, pH 6.8) containing sodium caseinate (Na-CN), 2 – 6% w/w, were investigated. The creaming kinetics, determined by multiple light scattering (Turbiscan), showed that the phase separation of Na-CN-stabilized emulsions was markedly dependent on the duration of the heat treatment. The differences between unheated and heated emulsions were attributed to heat-induced physicochemical changes in the aqueous Na-CN nanoparticles. The heat treatment caused protein degradation and changed the intact Na-CN concentration in the continuous phase. The emulsion structures, with varied extents of depletion flocculation, were well reflected by small and large deformation rheology. In the recombined Na-CN emulsions, the depletion attraction was weakened at low and moderate Na-CN concentrations (2% and 4% w/w) but was strengthened at high Na-CN concentration (6% w/w). The former structural change was predominantly due to reduced depletion attraction, whereas reduced depletion attraction and decreased continuous phase viscosity influenced the latter structural change. The intact Na-CN concentration in the continuous phase is determined by the heat-induced physicochemical changes of Na-CN nanoparticles, which played a significant role in the physical stability of the emulsions. The insights from this study can be used to create novel droplet sizes and protein particle sizes to manipulate the droplet/protein size ratio, and therefore the extent of droplet−droplet interactions. Graphical abstract: Highlights: Heating results in the decrease of particle size and viscosity of sodium caseinate. Phase separation of caseinate-stabilized emulsion markedly dependent on the heating time. Aggregation state and concentration of intact caseinate influence phase separation. Depletion attraction energy and continuous phase viscosity affect the emulsion stability.